2013
DOI: 10.4236/wjcd.2013.34a010
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes acutely determined by primary PCI in STEMI patients evaluated with a minimally invasive method

Abstract: Objective: Few studies are available on the hemodynamic changes acutely determined by Primary Percutaneous Coronary Intervention (PCI) in ST-Elevation Myocardial Infarction (STEMI) patients, probably for the difficult evaluation of hemodynamic variables in this acute setting. Therefore, the paper is to evaluate the variations of several hemodynamic parameters determined by PCI using PRAM (Pressure Recording Analytical Method), minimally invasive hemodynamic monitoring. Methods: We analyzed in 20 STEMI patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This device has been previously explored at our Institution in several acute cardiac conditions, such as heart failure (19,20) and ST-segment Elevation Myocardial Infarction (21), as well as in the postoperative phase of cardiac surgery. In the latter study, reduced perioperative values of Cardiac Cycle Efficiency demonstrated a negative prognostic impact at six months follow-up (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This device has been previously explored at our Institution in several acute cardiac conditions, such as heart failure (19,20) and ST-segment Elevation Myocardial Infarction (21), as well as in the postoperative phase of cardiac surgery. In the latter study, reduced perioperative values of Cardiac Cycle Efficiency demonstrated a negative prognostic impact at six months follow-up (4).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 20 years, the PRAM system has been used in different clinical conditions, both in our Center and in other Centers. In particular, in our Center it has been used to monitor patients with decompensated heart failure treated with ultrafiltration and diuretics (19,20), as well as to evaluate the beneficial effects of levosimendan (34), in patients with atrial fibrillation undergoing electrical cardioversion (35), in patients with ST-Elevation myocardial infarction treated with primary angioplasty (21), to monitor patients undergoing transcatheter aortic valve replacement (36,37), and in patients undergoing cardiac and vascular surgery, both intraoperatively (32) and in the postoperative course of cardiac surgery (4). In other Centers, the PRAM system has been used to monitor patients with septic shock (38), in patients undergoing major abdominal surgery (39) or cardiac surgery (1,40).…”
Section: Use Of Pram In Different Clinical Settingsmentioning
confidence: 99%
See 1 more Smart Citation